Formulasi Kajian Tafsir Nusantara - Muhammad Alwi HS; Asmullah Asmullah; Ahmad Nurkholis (Lajnah Pentashihan Mushaf Al-Qur'an, 2025)
This article presents the formulation of the study of Nusantara interpretation by positioning the treasures of Nusantara ulama as different, distinctive and unique works, while at the same time making the study of it appreciative. This effort is based on the argument that the presence of the study of Nusantara interpretation is a means for scholars to learn from the works of Nusantara ulama, and therefore scholars (should) make the works of Nusantara ulama the basis for developing the scientific study of interpretation. For this reason, this article applies the paradigm of Nusantara Islam in analyzing the study of Nusantara interpretation, from which it reveals several important aspects of the treasures of Nusantara interpretation. These aspects include script-language, presentation of interpretation, methodology, meaning, and others. From here, this article reveals that by holding the principle of being different and appreciative, the formulation of the study of Nusantara interpretation here invites scholars to be more creative in reading the works of Nusantara ulama. A creative way of reading means not allowing oneself to be constrained by existing theories, methods or paradigms, but the researcher freely creates and demonstrates contributions to the treasury of Nusantara interpretation.